Porous Nafion membranes - Joseph, Dickson; Busselmann, Julian; Harms, Corinna; Henkensmeier, Dirk; Larsen, Mikkel Juul; Dyck, Alexander; Jang, Jong Hyun; Kim, Hyoung-Juhn; Nam, Suk Woo (Elsevier BV, 2016)
By varying the amount of porogene (ortho-dichlorobenzene, ODB), and optimization of the dispersion process, two types of solvent cast Nafion membranes with an equivalent weight of 1100 g/mol sulfonic acid can be obtained reproducibly. One type is a dense membrane with a porous layer on one surface. The other membrane type shows a novel structure, consisting of small closed pores throughout the membrane and a single layer of large open pores on one side. In addition, some membranes showed a structural morphology between these two types, a membrane with a dense part and a porous part on top of each other. The latter membrane structure was not fully reproducible yet, but probably could be by carefully adjusting the formulation of the casting solution. Also the effect of the casting temperature on the morphology is shown. Fully porous membranes were characterized for their water permeability, ion conductivity, mechanical properties, their performance in the fuel cell and the hydrogen crossover. While the fully porous membranes are not expected to be part of a real fuel cell, we expect that the new morphologies will inspire applied research, e.g. in which the pores are filled with electrolyte or material or a catalyst is blended into the polymer. (C) 2016 Elsevier B.V. All rights reserved.